(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Patients with neurological damage often have emotional and behavioral changes. The use of cognitive behavioral therapy (CBT) has been suggested to manage symptoms of depression and anxiety in this population. The aim of this systematic review was to determine the applicability of CBT in patients with stroke, TBI and epilepsy. The databases PubMed, LILACS, SciELO Brazil, SCOPUS, PsycINFO, and EMBASE were consulted. Analyzed empirical articles, written in English, Spanish or Portuguese, with adults and published between 2002 and 2013. Among the 1397 articles found, 21 studies were evaluated. The population with the largest number of studies was TBI and the main goal of CBT is to promote improvement in depressive symptoms. According to the results, CBT in neurological patients suggests positive results, but requires investigations that provide evidence of therapeutic effect more reliable, more structured protocols, as well as follow-up studies